Comparison of the effect of shear bond strength with silane and other three chemical presurface treatments of a glass fiber-reinforced post on adhesion with a resin-based luting agent: An in vitro study - Vaibhavi Ramkrishna Belwalkar; Jaykumar Gade; Nikhil Purushottam Mankar (Wolters Kluwer Medknow Publications, 2016)
Background: Loss of retention has been cited to be the most common cause of the failure of postretained restoration with irreversible consequences when materials with different compositions are in intimate contact at the post/adhesive interface. With this background, a study was conducted to improve the adhesion at the resin phase of fiber posts using silane and other chemical pretreatments. Materials and Methods: Hundred glass fiber-reinforced posts were tested with 4 different protocols (n = 25) using silane as a control (Group A) and other three experimental groups, namely, Group B-20% potassium permanganate, Group C-4% hydrofluoric acid, and Group D-10% hydrogen peroxide were pretreated on the postsurface followed by silanization. These specimens were bonded with dual-polymerizing resin-based luting agent, which were then loaded at the crosshead speed of 1 mm/min to record the shear bond strength at the post/adhesive interface. The data were analyzed using one-way ANOVA test for multiple group comparisons and the post hoc Bonferroni test for pairwise comparisons (P < 0.05). Results: Group B showed more influence on the shear bond strength when compared to other protocols, respectively (P < 0.001). Conclusion: Alone silanization as a surface treatment did not improve the bond strength. Combination of chemical presurface treatments followed by silanization significantly enhanced the bond strength at the post/adhesive interface.